CARA AIRASIA MENCIPTAKAN KEKUASAAN DAN LOYALITAS PELANGGANNYA - Syafrianti, Monika; Hendra Riofita (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2024)
To analyze the strategies implemented by AirAsia in creating customer power and loyalty. This article discusses how AirAsia has succeeded in creating power and customer loyalty. Research findings show that AirAsia has succeeded in building customer power through competitive pricing strategies, an extensive route network, and an attractive loyalty program. Apart from that, AirAsia has also succeeded in creating customer loyalty through consistent service quality, personalization of the customer experience, and the use of advanced technology. This study advances our knowledge of successful marketing techniques in the aviation sector.